Worldwide variations in COVID-19 vaccination policies and practices in liver transplant settings: results of a multi-society global survey - Di Maira, Tommaso; Vinaixa, Carmen; Izzy, Manhal; Paolo Russo, Francesco; Kirchner, Varvara A.; Rammohan, Ashwin; Belli, Luca Saverio; Polak, Wojciech Grzegorz; Berg, Thomas; Berenguer, Marina (Frontiers in Transplantation, 2024)
Background Despite the WHO's report of 24 available SARS-CoV-2 vaccines, limited data exist regarding vaccination policies for liver transplant (LT) patients. To address this, we conducted a global multi-society survey (EASL-ESOT-ELITA-ILTS) in LT centers. Methods A digital questionnaire assessing vaccine policies, safety, efficacy, and center data was administered online to LT centers. Results Out of 168 responding centers, 46.4%, 28%, 13.1%, 10.7%, and 1.8% were from European, American, Western Pacific, Southeast Asian, and Eastern Mediterranean Regions. Most LT centers prioritized COVID-19 vaccine access for LT patients (76%) and healthcare workers (86%), while other categories had lower priority (30%). One-third of responders recommended mRNA vaccine exclusively, while booster doses were widely recommended (81%). One-third conducted post-vaccine liver function tests post COVID-19 vaccine. Only 16% of centers modified immunosuppression, and mycophenolate discontinuation or modification was the main approach. Side effects were seen in 1 in 1,000 vaccinated patients, with thromboembolism, acute rejection, and allergic reaction being the most severe. mRNA showed fewer side effects (−3.1, p = 0.002). Conclusion COVID-19 vaccines and booster doses were widely used among LT recipients and healthcare workers, without a specific vaccine preference. Preventative immunosuppression adjustment post-vaccination was uncommon. mRNA vaccines demonstrated a favorable safety profile in this population.